The Mediating Role Of Job Satisfaction: The Impact Of Organizational Commitment On Employee Intention To Quit - Mochammad Munir Rachman; Ch. Menuk Sri Handayani; Sugijanto Sugijanto (Department of Management, Faculty of Economics and Business, Brawijaya University, 2022)
The purpose of this study was to investigate how of job satisfaction that mediates the intention to quit employees from the company that determined by organizational commitment. The study used the explanatory method, and the sample was based on a questionnaire distributed by 120 respondents with SEM analysis. The results of this study indicate that organizational commitment and job satisfaction have a positive and significant effect on intention to quit. The positive effect of organizational commitment shows that employees have a high desire to quit. Opportunities to leave the organization are getting stronger because company leaders are aware of their behavior. The positive effect of organizational commitment on job satisfaction has also increased. Actions taken by employees are more directed towards expectations because extrinsically job satisfaction has an important role for the work itself. It strengthens the emotions of employees to work better. Another finding, also states that organizational commitment mediated by job satisfaction also responds to the employee's desire to quit, this positively also places the work they are engaged in, and contributes practically because high job satisfaction generally results in high employee retention rates.